Leadership development in governments of the United Arab Emirates: Re-framing a wicked problem. Issue 2 (July 2017) - Mathias, Megan
Developing the next generation of leaders in government is seen as a strategic challenge of national importance in the United Arab Emirates (UAE). This article examines the wicked nature of the UAE's leadership development challenge, identifying patterns of complexity, uncertainty, and divergence in the strategic intentions underlying current leadership development efforts. It then explores the potential impact of re-framing leadership development programmes for government employees using the concept of 'public leadership'. Responding to calls in the literature for situated and context-sensitive explorations of leadership, it draws upon recent empirical research and literature to conceptualise public leadership for the UAE before identifying three potential contributions: an orientation towards collective, public values; a connection into needed skills frameworks; and access to innovations in the design of public leadership development interventions. The article concludes that the re-framing of 'public leadership' has the potential to help make substantial progress on the UAE's strategic leadership development challenge, but is not a silver bullet. Further research on both the concept, and its impact if adopted for leadership development programmes, will be required.